How do employment relationships enhance firm innovation? The role of human and social capital. Issue 9 (15th May 2017) - Bornay-Barrachina, Mar; López-Cabrales, Alvaro; Valle-Cabrera, Ramón
Abstract: Aiming to explore the effect of human resource management on innovation, this study examined how employment relationships (ER), human capital and social capital work together in influencing innovation in a sample of Spanish firms. We defined an indirect effects model in which both human and social capital mediate between ERs and innovation. We also expected that social capital would enhance human capital. Tests on a sample of 160 innovative Spanish firms confirmed that ERs are not directly associated with innovation. Nevertheless, there is an indirect effect of the mutual investment employment model on innovation through human and social capital. Finally, we observed a positive effect of social capital on human capital.